A framework for a network-level performance measurement system in SME networks. (20th June 2008) - Varamaki, Elina; Kohtamaki, Marko; Jarvenpaa, Marko; Vuorinen, Tero; Laitinen, Erkki; Sorama, Kirsti; Wingren, Tom; Vesalainen, Jukka; Helo, Petri; Tuominen, Tommi; Pihkala, Timo; Tenhunen, Jarkko
The present study aims to present a theoretical framework for a network-level performance measurement system. The suggested framework for the performance measurement system is composed of the factors that enable and cause the productivity and profitability of the network form of organisation. The framework developed in this study can be divided into six subdimensions: (1) network culture, (2) resources and competences, (3) models of action, (4) internal processes, (5) customer perspective and (6) financial indicators of the network. We argue that this framework provides research opportunities to study the performance of the network form of organisation; but even more importantly, it provides a unique framework to analyse and develop network organisations in practice.